Preparation method of silicon carbide ceramic and silicon carbide ceramic

By using non-toxic and environmentally friendly materials such as isobutene-maleic anhydride copolymer, combined with nanoparticles and fibers, the preparation process of silicon carbide ceramics is simplified, and the problems of toxic additives and high operation difficulty in the prior art are solved, efficient and safe preparation of silicon carbide ceramics is achieved, and the toughness and mechanical properties of the material are improved.

CN119707497APending Publication Date: 2025-03-28SOLOMON (CHANGZHOU) ALLOY NEW MATERIAL CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411909419.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing silicon carbide ceramic preparation methods use a wide variety of organic additives and are mostly toxic, with high process operation difficulty and risk, making it difficult to meet the application needs of mobile phone back panels.

Method used

Isobutylene-maleic anhydride copolymer (Isobam-104) is used as the main component of the gel system, combined with dispersant, water, silicon carbide ceramic powder, second phase nanoparticles and silicon carbide fibers, and non-toxic and environmentally friendly silicon carbide ceramics are prepared through ball mill mixing, vacuum defoaming, spontaneous solidification molding, wet blank drying, glue discharge and vacuum sintering.

Benefits of technology

It realizes the non-toxic and environmentally friendly preparation of silicon carbide ceramics, simplifies the process flow, reduces the difficulty and danger of operation, improves the fracture toughness and mechanical properties of the material, and is suitable for complex structural parts such as mobile phone back panels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707497A_ABST
    Figure CN119707497A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of silicon carbide ceramic and the silicon carbide ceramic, and the preparation method of the silicon carbide ceramic comprises the following steps: sequentially carrying out ball-milling mixing, vacuum defoaming, spontaneous solidification forming, wet blank drying, glue discharging and vacuum sintering on ceramic slurry to obtain the silicon carbide ceramic, the ceramic slurry comprises an isobutylene maleic anhydride copolymer, a dispersant, deionized water, silicon carbide ceramic powder, second-phase nanoparticles and silicon carbide fibers. The isobutylene-maleic anhydride copolymer (Isobam-104) is introduced into a gel system, so that the gel system is non-toxic and environment-friendly and has a spontaneous solidification effect, the variety and content of organic additives are greatly reduced, a green body is not easy to peel and crack, and the difficulty of mold design and molding operation is reduced; meanwhile, the second-phase nano ceramic particles and the silicon carbide fibers are mixed for use, so that the effect of toughening the silicon carbide ceramic can be achieved, and the sintered silicon carbide ceramic is firm and resistant to falling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicon carbide ceramics, and in particular to a preparation method of silicon carbide ceramics and the silicon carbide ceramics. Background Art

[0002] Smartphones have become the most commonly used communication, social and photography tools for humans due to their rich and powerful functions, bringing great convenience to human life. The back panel of a mobile phone is an important part of the external structure of a mobile phone. It not only protects the internal components of the mobile phone from external physical damage (such as collisions and scratches), but is also often used as an important element of the mobile phone's appearance design, reflecting the brand characteristics, design concepts and user's personal choices of the mobile phone. With the development of smartphones, there are mobile phone back panels made of a variety of different materials, such as metal, plastic, glass, fiberglass and ceramic. Among them, ceramics have gradually become the main material for mobile phone back panels in the 5G communication era due to their good mechanical properties, jade-like texture, and very small dielectric constant, meeting users' demand for high-end textured mobile phones.

[0003] At present, zirconia ceramics are the main material for making ceramic mobile phone back panels. They have excellent mechanical properties, are easy to color, and have good texture, but they also have obvious disadvantages. 1. Zirconia has a high density of 6g / cm 3 , close to steel, so it will significantly increase the weight of the mobile phone and it is difficult to meet the lightweight requirements; 2. The dielectric constant of zirconium oxide is relatively high (~34), which has a certain impact on 5G signal transmission; 3. The thermal conductivity of zirconium oxide is not high enough, usually only about 3W / m·K at room temperature, and the heat dissipation effect is not good enough, which can easily affect the operation of the mobile phone.

[0004] Compared with zirconium oxide, silicon carbide ceramics have a lower density (3.2g / cm 3 The dielectric constant is small (9-10), and the thermal conductivity is as high as 50W / m·K or more, which can meet the requirements of lightweight, 5G signal transmission and high-speed operation of mobile phones. Although the fracture toughness is low (4MPa·m 1 / 2 However, the toughening effect can be achieved by adding nanoparticles and silicon carbide short fibers to meet the application of mobile phone back panels. However, silicon carbide ceramics are very hard and difficult to process. Therefore, for thin-walled and complex-shaped structural parts such as mobile phone back panels, it is necessary to choose a process that can form complex-shaped blanks so that the sintered ceramic back panel is close to the size of the final product, which can greatly reduce the amount of subsequent processing and save time and cost.

[0005] Gel injection molding is a new type of ceramic molding technology invented in the early 1990s. It usually generates a three-dimensional network structure through the polymerization reaction between organic monomers and cross-linking agents, locks the powder in it, and solidifies it in situ. It can achieve near-net-size molding of complex-shaped ceramic blanks, and the density of the blanks is uniform, which is suitable for the molding of ceramic mobile phone back panels. Some researchers have used this method to mold silicon carbide ceramics: such as patent 202210830400.X "A method for preparing silicon carbide ceramics by pressureless sintering by gel injection molding", using silane coupling agents to modify the surface of silicon carbide powder, using acrylamide as a monomer, N,N-methylenebisacrylamide as a cross-linking agent, ammonium bisulfite and ammonium persulfate as redox initiators, gel injection molding silicon carbide, and adding tert-butylcatechol, phenothiazine, hydroquinone and diphenylamine as inhibitors to the system, which can prolong the polymerization time and improve the uniformity of curing. However, the system uses many types of organic additives, more than 10, and most of them are toxic and harmful to the human body and the environment. In addition, the acrylamide gel system will also undergo oxygen inhibition, that is, contact with oxygen should be avoided as much as possible during curing. These have greatly increased the difficulty and danger of the process operation and are not suitable for large-scale use.

[0006] In view of this, developing a non-toxic, environmentally friendly, simple and efficient silicon carbide ceramic gel injection molding method is crucial for its application in mobile phone back panels. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing silicon carbide ceramics and silicon carbide ceramics, and to improve the fracture toughness of silicon carbide ceramics.

[0008] The present invention is achieved in that:

[0009] In a first aspect, the present invention provides a method for preparing silicon carbide ceramics, comprising: subjecting a ceramic slurry to ball milling mixing, vacuum degassing, spontaneous solidification molding, wet blank drying, binder removal and vacuum sintering in sequence to obtain the silicon carbide ceramics, wherein the ceramic slurry comprises isobutylene maleic anhydride copolymer, a dispersant, water, silicon carbide ceramic powder, second phase nanoparticles and silicon carbide fibers.

[0010] In an optional embodiment, in the ceramic slurry, the ratio of the mass of the isobutylene maleic anhydride copolymer to the total mass of the silicon carbide ceramic powder, the second phase nanoparticles and the silicon carbide fibers is 2% to 5%.

[0011] In an optional embodiment, the dispersant is ammonium polyacrylate, and the ratio of the mass of the dispersant to the total mass of the ceramic powder and the silicon carbide fiber in the ceramic slurry is 0.2% to 2%.

[0012] In an optional embodiment, the particle size of the silicon carbide ceramic powder is 0.5 μm to 8 μm, and the purity is more than 99%;

[0013] And / or, the second phase nanoparticles are selected from at least one of TiN, SiB6 and ZrB2, with a particle size of 50nm to 100nm and a purity of more than 99%;

[0014] And / or, the silicon carbide fibers have an average diameter of 0.9 μm to 1.1 μm and an average length of 30 μm to 300 μm.

[0015] In an optional embodiment, the mass ratio of the second phase nanoparticles to the silicon carbide fibers is 1:(0.8-1.2);

[0016] And / or, the water is deionized water;

[0017] and / or, the ratio of the total mass of the second phase nanoparticles and the silicon carbide fibers to the mass of the silicon carbide powder is 4% to 6%;

[0018] And / or, the volume solid content of the ceramic slurry is 46%-60%.

[0019] In an optional embodiment, the preparation of the ceramic slurry includes: mixing the isobutylene maleic anhydride copolymer, a dispersant and water to obtain a premixed solution;

[0020] The premixed liquid, silicon carbide ceramic powder, second phase nanoparticles, silicon carbide fibers, and silicon carbide ceramic grinding balls are added into a ball mill, and then planetary ball milling is performed to obtain a ceramic slurry; the ball-to-material ratio of the planetary ball mill is (4-6):1, and the ball milling time is 18h-24h.

[0021] In an optional embodiment, the vacuum degassing method is stirring degassing, the vacuum degree is less than -0.1MPa, and the degassing time is 10min-20min.

[0022] And / or, the molding step comprises: injecting the defoamed ceramic slurry into a mold coated with a release agent, and demolding after spontaneous solidification to obtain a wet blank;

[0023] In an optional embodiment, the mold material is one of silicone, organic glass, graphite, metal, and plastic;

[0024] and / or, the release agent is one of silicone oil or butter grease;

[0025] And / or, the spontaneous solidification molding condition is at room temperature, in an air environment, and the curing molding time is 2h to 4h;

[0026] And / or, the wet billet drying includes sequentially performing room temperature drying and heating drying.

[0027] In an optional embodiment, the debinding step includes: heating to 450°C to 550°C at a rate of 1.5°C / min to 2.5°C / min, keeping the temperature for 1h to 3h, then heating to 650°C to 750°C at a rate of 2°C / min to 3°C / min, keeping the temperature for 2 to 4h, and the atmosphere is an oxygen-containing atmosphere;

[0028] And / or, the temperature of the vacuum sintering step is 1900° C. to 2000° C., and the holding time is 1 hour to 2 hours.

[0029] In a second aspect, the present invention provides a method for preparing silicon carbide ceramics, which is prepared by the method described in any one of the aforementioned embodiments.

[0030] The present invention has the following beneficial effects:

[0031] The gel system of the embodiment of the present invention introduces isobutylene-maleic anhydride copolymer (Isobam-104), which is a non-toxic and environmentally friendly reagent, harmless to the human body, and has high operational safety. The system has a spontaneous solidification effect, that is, it is not necessary to add monomers, cross-linking agents, initiators, and catalysts like the commonly used gel systems, which greatly reduces the types and contents of organic additives, has a simple process, and is easy to discharge glue; the Isobam gel system used does not have an oxygen inhibition effect, the solidification molding of the slurry can be carried out in the air, the green body is not easy to peel and crack, and the difficulty of mold design and molding operation is reduced.

[0032] In the embodiment of the present invention, the second phase nano-ceramic particles and silicon carbide fibers are mixed and used, which can achieve the effect of toughening the silicon carbide ceramics, making the sintered silicon carbide ceramics strong and resistant to falling. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 Schematic diagram of the mobile phone back panel mold used in the embodiments and comparative examples.

[0035] Figure 2 This is a photo of the green blank obtained after debinding of the silicon carbide ceramic mobile phone back panel prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0037] An embodiment of the present invention provides a method for preparing silicon carbide ceramics, comprising: sequentially subjecting a ceramic slurry to ball milling mixing, vacuum degassing, spontaneous solidification molding, wet blank drying, binder removal and vacuum sintering to obtain the silicon carbide ceramics, wherein the ceramic slurry comprises an isobutylene maleic anhydride copolymer, a dispersant, water, silicon carbide ceramic powder, second phase nanoparticles and silicon carbide fibers.

[0038] The gel system of the embodiment of the present invention introduces isobutylene-maleic anhydride copolymer (Isobam-104), which is a non-toxic and environmentally friendly reagent, harmless to the human body, and has high operational safety. The system has a spontaneous solidification effect, that is, it is not necessary to add monomers, cross-linking agents, initiators, and catalysts like the commonly used gel systems, which greatly reduces the types and contents of organic additives, has a simple process, and is easy to discharge glue; the Isobam gel system used does not have an oxygen inhibition effect, the solidification molding of the slurry can be carried out in the air, the green body is not easy to peel and crack, and the difficulty of mold design and molding operation is reduced.

[0039] In the embodiment of the present invention, the second phase nano-ceramic particles and silicon carbide fibers are mixed and used, which can achieve the effect of toughening the silicon carbide ceramics, making the sintered silicon carbide ceramics strong and resistant to falling.

[0040] It should be noted that the silicon carbide ceramics in the present application can be prepared into various shapes, such as a mobile phone back cover or other shapes, according to different mold shapes.

[0041] In an optional embodiment, in the ceramic slurry, the ratio of the mass of the isobutylene maleic anhydride copolymer to the total mass of the silicon carbide ceramic powder, the second phase nanoparticles and the silicon carbide fibers is 2% to 5%.

[0042] The amount of isobutylene maleic anhydride copolymer will affect the mechanical properties, shrinkage and microstructure of silicon carbide ceramics. The amount of isobutylene maleic anhydride copolymer should be properly adjusted to balance the mechanical properties such as strength, hardness and toughness of the material with the shrinkage.

[0043] In an optional embodiment, the dispersant is ammonium polyacrylate, and the ratio of the mass of the dispersant to the total mass of the ceramic powder and the silicon carbide fiber in the ceramic slurry is 0.2% to 2%.

[0044] Isobam-104 has a dispersing function after being dissolved in water and can be used as a dispersant at the same time, so the amount of dispersant added can be reduced, which is beneficial to reducing the viscosity of the slurry.

[0045] In an optional embodiment, the particle size of the silicon carbide ceramic powder is 0.5 μm to 8 μm, and the purity is more than 99%;

[0046] And / or, the second phase nanoparticles are selected from at least one of TiN, SiB6 and ZrB2, with a particle size of 50nm to 100nm and a purity of more than 99%;

[0047] And / or, the average diameter of the silicon carbide fiber is 0.9 μm to 1.1 μm, and the average length is 30 μm to 300 μm;

[0048] And / or, the water is deionized water.

[0049] The particle size of the second phase nanoparticles is much smaller than that of silicon carbide ceramic powder, and can effectively fill the gaps between the particles to form a denser structure. During the sintering process, they can act as crystal nuclei to promote uniform nucleation and growth of grains and reduce grain coarsening. They can also reduce grain boundary defects and increase the strength of grain boundaries, thereby improving the overall mechanical properties of the material.

[0050] Silicon carbide fiber can form a three-dimensional network structure in the material, which can effectively prevent the expansion of cracks and improve the material's ability to resist crack expansion; it can serve as a skeleton to support the material structure, reduce the formation of pores, and improve density.

[0051] The second phase nanoparticles and silicon carbide fibers have a synergistic effect and can more effectively improve the toughness of silicon carbide ceramics.

[0052] In an optional embodiment, the mass ratio of the second phase nanoparticles to the silicon carbide fibers is 1:(0.8-1.2);

[0053] and / or, the ratio of the total mass of the second phase nanoparticles and the silicon carbide fibers to the mass of the silicon carbide powder is 4% to 6%;

[0054] And / or, the volume solid content of the ceramic slurry is 46%-60%.

[0055] Excessive use of second-phase nanoparticles or silicon carbide fibers, or too high a solid content, will result in excessive slurry viscosity, affect fluidity, cause fiber or nanoparticle agglomeration, and may lead to increased porosity and reduced thermal stability.

[0056] In an optional embodiment, the preparation of the ceramic slurry includes: mixing isobutylene maleic anhydride copolymer, a dispersant and water to obtain a premixed solution; the mixing method can be ultrasonic dispersion or magnetic stirring for 10-20 minutes;

[0057] The premixed liquid, silicon carbide ceramic powder, second phase nanoparticles, silicon carbide fibers, and silicon carbide ceramic grinding balls are added into a ball mill, and then planetary ball milling is performed to obtain a ceramic slurry; the ball-to-material ratio of the planetary ball mill is (4-6):1, and the ball milling time is 18h-24h.

[0058] Preparing the premixed liquid first and then ball milling is beneficial to the uniform mixing of the ceramic slurry.

[0059] In an optional embodiment, the vacuum degassing method is stirring degassing, the vacuum degree is less than -0.1MPa, and the degassing time is 10min-20min.

[0060] And / or, the forming step comprises: injecting the defoamed ceramic slurry into a mold coated with a release agent, and demolding after spontaneous solidification to obtain a wet blank.

[0061] In an optional embodiment, the mold material is one of silicone, organic glass, graphite, metal, and plastic; preferably silicone;

[0062] and / or, the release agent is one of silicone oil or butter grease;

[0063] And / or, the spontaneous solidification molding condition is at room temperature, in an air environment, and the curing molding time is 2h to 4h;

[0064] And / or, the wet blank drying includes room temperature drying and heating drying in sequence, the drying time at room temperature is 16 to 24 hours, and the drying temperature in the blast drying oven is 40 to 70° C., until the weight of the blank no longer changes.

[0065] In an optional embodiment, the debinding step includes: heating to 450°C to 550°C at a rate of 1.5°C / min to 2.5°C / min, keeping the temperature for 1h to 3h, then heating to 650°C to 750°C at a rate of 2°C / min to 3°C / min, keeping the temperature for 2 to 4h, and the atmosphere is an oxygen-containing atmosphere;

[0066] And / or, the temperature of the vacuum sintering step is 1900° C. to 2000° C., and the holding time is 1 hour to 2 hours.

[0067] The debinding step of the embodiment of the present application adopts a segmented heating and insulation method, combined with a smaller heating rate, which is beneficial to improve the temperature uniformity of various parts of the blank and reduce the deformation or cracking of the blank caused by uneven stress distribution inside the ceramic matrix due to excessive heating.

[0068] An embodiment of the present invention further provides a method for preparing silicon carbide ceramics, which is prepared by the method described in any one of the aforementioned embodiments.

[0069] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0070] Example 1

[0071] A method for forming a non-toxic and environmentally friendly silicon carbide ceramic mobile phone back panel by spontaneous solidification, specifically comprising the following steps:

[0072] 1. Prepare the premixed solution: weigh 1.5g of Isobam-104 and 0.7g of ammonium polyacrylate and dissolve them in 22g of deionized water. Stir magnetically for 15min.

[0073] 2. Slurry preparation and ball milling: weigh 69 g of commercial silicon carbide powder with a particle size of 4 μm, 2 g of TiN particles with a particle size of 50 nm, and 2 g of silicon carbide fibers with an average diameter of 1 μm and an average length of 100 μm, add them to the premixed liquid in step 1, and add 365 g of silicon carbide grinding balls, and ball mill at a speed of 200 r / min for 18 h to obtain silicon carbide ceramic slurry.

[0074] 3. Vacuum stir to remove bubbles for 15 minutes.

[0075] 4. Inject the defoamed slurry into a silicone mold coated with silicone oil. The mold diagram is as follows: Figure 1 As shown, it spontaneously solidifies at room temperature in air, the curing time is 4 hours, and then demolding.

[0076] 5. Dry the wet blank obtained in step 4 at room temperature for 20 hours, then place it in a forced air drying oven, dry it at 40°C for 12 hours, then raise the temperature to 60°C and dry it until the weight remains unchanged.

[0077] 6. Place the ceramic blank obtained in step 5 into a muffle furnace, heat it to 500°C at a rate of 2°C / min, keep it warm for 2h, then heat it to 700°C at a rate of 3°C / min, keep it warm for 2h, and obtain a silicon carbide ceramic blank with a smooth and dense surface, a thickness of 0.95mm, and an appearance of Figure 2 shown.

[0078] 7. Place the green blank obtained in step 6 into a vacuum sintering furnace and sinter without pressure at 1960°C for 1 hour to obtain a silicon carbide ceramic mobile phone back panel with a bending strength of 550 MPa and a fracture toughness of 7.6 MPa·m 1 / 2 .

[0079] Example 2

[0080] A method for forming a non-toxic and environmentally friendly silicon carbide ceramic mobile phone back panel by spontaneous solidification, specifically comprising the following steps:

[0081] 1. Prepare the premixed solution: weigh 2.6g of Isobam-104 and 1.3g of ammonium polyacrylate and dissolve them in 22g of deionized water. Stir magnetically for 20min.

[0082] 2. Slurry preparation and ball milling: weigh 63g of commercial silicon carbide powder with a particle size of 1μm, 1.7g of SiB6 particles with a particle size of 50nm, and 1.7g of silicon carbide fibers with a diameter of 1μm and a length of 200μm, add them to the premixed liquid in step 1, and add 332g of silicon carbide grinding balls, and ball mill at a speed of 200r / min for 24h to obtain silicon carbide ceramic slurry.

[0083] 3. Vacuum stir to remove bubbles for 20 minutes.

[0084] 4. Inject the defoamed slurry into a silicone mold coated with silicone oil. The mold diagram is as follows: Figure 1 As shown, it spontaneously solidifies at room temperature in air, the curing time is 4 hours, and then demolding.

[0085] 5. Dry the wet blank obtained in step 4 at room temperature for 24 hours, then place it in a forced air drying oven, dry it at 40°C for 16 hours, then raise the temperature to 60°C and dry it until the weight remains unchanged.

[0086] 6. Place the ceramic blank obtained in step 5 into a muffle furnace, heat it to 500°C at a rate of 2°C / min, keep it warm for 3 hours, then heat it to 700°C at a rate of 2°C / min, keep it warm for 3 hours, and obtain a silicon carbide ceramic blank with a smooth and dense surface and a thickness of 0.9 mm.

[0087] 7. Place the green blank obtained in step 6 into a vacuum sintering furnace and sinter without pressure at 1940°C for 1.5 hours to obtain a silicon carbide ceramic mobile phone back panel with a bending strength of 570 MPa and a fracture toughness of 7.8 MPa·m 1 / 2 .

[0088] Example 3

[0089] A method for forming a non-toxic and environmentally friendly silicon carbide ceramic mobile phone back panel by spontaneous solidification, specifically comprising the following steps:

[0090] 1. Prepare the premixed solution: weigh 3.1g of Isobam-104 and dissolve 1.26g of ammonium polyacrylate in 22g of deionized water, and stir magnetically for 20min.

[0091] 2. Slurry preparation and ball milling: weigh 60g of commercial silicon carbide powder with a particle size of 0.5μm, 1.6g of TiN particles with a particle size of 50nm, and 1.6g of silicon carbide fibers with a diameter of 1.1μm and a length of 300μm, add them to the premixed liquid in step 1, and add 316g of silicon carbide grinding balls, and ball mill at a speed of 220r / min for 24h to obtain silicon carbide ceramic slurry.

[0092] 3. Vacuum stir to remove bubbles for 20 minutes.

[0093] 4. Inject the defoamed slurry into a silicone mold coated with silicone oil. The mold diagram is as follows: Figure 1 As shown, it spontaneously solidifies at room temperature in air, the curing time is 4 hours, and then demolding.

[0094] 5. Dry the wet blank obtained in step 4 at room temperature for 24 hours, then place it in a forced air drying oven, dry it at 40°C for 16 hours, then raise the temperature to 60°C and dry it until the weight remains unchanged.

[0095] 6. Place the ceramic blank obtained in step 5 into a muffle furnace, heat it to 500°C at a rate of 2°C / min, keep it warm for 3 hours, then heat it to 700°C at a rate of 2°C / min, keep it warm for 4 hours, and obtain a silicon carbide ceramic blank with a smooth and dense surface and a thickness of 0.85 mm.

[0096] 7. Place the green blank obtained in step 6 into a vacuum sintering furnace and sinter without pressure at 1940°C for 1 hour to obtain a silicon carbide ceramic mobile phone back panel with a bending strength of 590 MPa and a fracture toughness of 8.1 MPa·m 1 / 2 .

[0097] Comparative Example 1

[0098] This comparative example provides a non-toxic and environmentally friendly method for spontaneously solidifying and forming a silicon carbide ceramic mobile phone back panel. The main difference from Example 1 is that TiN particles and silicon carbide fibers are not added to the silicon carbide ceramic slurry.

[0099] Comparative Example 2

[0100] This comparative example provides a non-toxic and environmentally friendly method for spontaneously solidifying and forming a silicon carbide ceramic mobile phone back panel. The main difference from Example 1 is that silicon carbide fibers are not added to the silicon carbide ceramic slurry.

[0101] Comparative Example 3

[0102] This comparative example provides a non-toxic and environmentally friendly method for spontaneously solidifying and forming a silicon carbide ceramic mobile phone back panel. The main difference from Example 1 is that no TiN particles are added to the silicon carbide ceramic slurry.

[0103] Comparative Example 4

[0104] This comparative example provides a non-toxic and environmentally friendly method for spontaneously solidifying and forming a silicon carbide ceramic mobile phone back panel, which is different from Example 1 mainly in that TiN particles are replaced by AlN particles.

[0105] Comparative Example 5

[0106] This comparative example provides a non-toxic and environmentally friendly method for spontaneously solidifying and forming a silicon carbide ceramic mobile phone back panel. The main difference from Example 1 is that the silicon carbide fiber is replaced by alumina fiber.

[0107] Comparative Example 6

[0108] This comparative example provides a non-toxic and environmentally friendly method for spontaneously solidifying and forming a silicon carbide ceramic mobile phone back panel, which differs from Example 1 mainly in that Isobam-104 is replaced by PVA.

[0109] The thickness and relative density of the silicon carbide ceramic blanks obtained after debinding in the above embodiments and comparative examples, as well as the bending strength and fracture toughness of the prepared mobile phone back panels were tested, and the results are shown in Table 1.

[0110] Table 1

[0111]

[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing silicon carbide ceramics, characterized in that: include: The ceramic slurry is subjected to ball milling mixing, vacuum degassing, spontaneous solidification molding, wet blank drying, binder removal and vacuum sintering in sequence to obtain the silicon carbide ceramic, wherein the ceramic slurry includes isobutylene maleic anhydride copolymer, dispersant, water, silicon carbide ceramic powder, second phase nanoparticles and silicon carbide fibers.

2. The method for preparing silicon carbide ceramics according to claim 1, characterized in that: In the ceramic slurry, the mass ratio of the isobutylene maleic anhydride copolymer to the total mass of the silicon carbide ceramic powder, the second phase nanoparticles and the silicon carbide fibers is 2% to 5%.

3. The method for preparing silicon carbide ceramics according to claim 1, characterized in that: The dispersant is ammonium polyacrylate, and the ratio of the mass of the dispersant to the total mass of the ceramic powder and the silicon carbide fiber in the ceramic slurry is 0.2% to 2%.

4. The method for preparing silicon carbide ceramics according to claim 1, characterized in that: The particle size of silicon carbide ceramic powder is 0.5μm to 8μm, and the purity is more than 99%; And / or, the second phase nanoparticles are selected from at least one of TiN, SiB6 and ZrB2, with a particle size of 50nm to 100nm and a purity of more than 99%; And / or, the average diameter of the silicon carbide fiber is 0.9 μm to 1.1 μm, and the average length is 30 μm to 300 μm; And / or, the water is deionized water.

5. The method for preparing silicon carbide ceramics according to claim 1, characterized in that: The mass ratio of the second phase nanoparticles to silicon carbide fibers is 1:(0.8-1.2); and / or, the ratio of the total mass of the second phase nanoparticles and the silicon carbide fibers to the mass of the silicon carbide powder is 4% to 6%; And / or, the volume solid content of the ceramic slurry is 46%-60%.

6. The method for preparing silicon carbide ceramics according to claim 1, characterized in that: The preparation of the ceramic slurry comprises: mixing an isobutylene maleic anhydride copolymer, a dispersant and water to obtain a premixed liquid; The premixed liquid, silicon carbide ceramic powder, second phase nanoparticles, silicon carbide fibers, and silicon carbide ceramic grinding balls are added into a ball mill, and then planetary ball milling is performed to obtain a ceramic slurry; the ball-to-material ratio of the planetary ball mill is (4-6):1, and the ball milling time is 18h-24h.

7. The method for preparing silicon carbide ceramics according to claim 1, characterized in that: The vacuum defoaming method is stirring defoaming, the vacuum degree is less than -0.1MPa, and the defoaming time is 10min-20min; And / or, the spontaneous solidification molding step includes: injecting the defoamed ceramic slurry into a mold coated with a release agent, and demolding after spontaneous solidification molding to obtain a wet blank.

8. The method for preparing silicon carbide ceramics according to claim 7, characterized in that: The material of the mold is one of silicone, organic glass, graphite, metal and plastic; and / or, the release agent is one of silicone oil or butter grease; And / or, the spontaneous solidification molding condition is at room temperature, in an air environment, and the curing molding time is 2h to 4h; And / or, the wet billet drying includes sequentially performing room temperature drying and heating drying.

9. The method for preparing silicon carbide ceramics according to claim 1, characterized in that: The debinding step includes: heating to 450°C to 550°C at a rate of 1.5°C / min to 2.5°C / min, keeping the temperature for 1h to 3h, then heating to 650°C to 750°C at a rate of 2°C / min to 3°C / min, keeping the temperature for 2 to 4h, and the atmosphere is an oxygen-containing atmosphere; And / or, the temperature of the vacuum sintering step is 1900° C. to 2000° C., and the holding time is 1 hour to 2 hours.

10. A silicon carbide ceramic, characterized in that: Prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A method for preparing silicon carbide ceramics by gel casting and pressureless sintering.

    CN114988880B